Apollo & Vulcan : the art markets in Italy, 1400-1700 - Guerzoni, Guido (East Lansing : Michigan State University Press, 2011)
Guido Guerzoni presents the results of fifteen years of research into one of the more hotly debated topics among historians of art and of economics: the history of art markets. Dedicating equal attention to current thought in the fields of economics, economic history, and art history, Guerzoni offers a broad and far-reaching analysis of the Italian scene, highlighting the existence of different forms of commercial interchange and diverse kinds of art markets. In doing so he ranges beyond painting and sculpture, to examine as well the economic drivers behind architecture, decorative and sumptuary arts, and performing or ephemeral events. Organized by thematic areas (the ethics and psychology of consumption, an analysis of the demand, labor markets, services, prices, laws) that cover a large chronological period (from the 15th through the 17th century), various geographical areas, and several institution typologies, this book offers an exhaustive and up-to-date study of an increasingly fascinating topic.
""5. Services: The Economy of the Feast and the Feast of the Economyâ€?Some Thoughts on Ephemera """"6. Prices: Known Facts and Unresolved Problems ""; ""7. The Laws: The Birth of Cultural Heritage and the Impact of Preservation Laws on the Art Trade ""; ""Notes""; ""Bibliography""; ""Acknowledgments""; ""Index""
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Translated from the Italian.
JSTOR
Keywords: Art -- Economic aspects -- Italy -- History; Art -- Marketing; Art -- Commercialisation; art market; ART -- History -- Renaissance; Art -- Economic aspects; Art -- Marketing; Italy; History